2009
DOI: 10.1182/blood-2008-09-179416
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of mast cells in pruritogenesis in patients with myeloproliferative disorders

Abstract: Pruritus is a common symptom in patients with Philadelphia chromosomenegative myeloproliferative disorders (MPDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 46 publications
2
77
0
2
Order By: Relevance
“…In this regard, there is recent evidence that an increased output of CD34 + cell-derived mast cells in patients with myeloproliferative neoplasms plays a role in the etiogenesis of pruritus, possibly through the release of prostaglandin D2 and increased levels of IL-31. 43 Overall, the results of this study indicate that PV basophils are constitutively activated and hypersensitive to IL-3, favoring a direct role of JAK2V617F mutation. They also lend support to the hypothesis that activated basophils contribute to pruritus in PV patients and that JAK2 inhibitors might be effective in countering this agonizing and usually treatment-insensitive symptom.…”
Section: Discussionmentioning
confidence: 55%
“…In this regard, there is recent evidence that an increased output of CD34 + cell-derived mast cells in patients with myeloproliferative neoplasms plays a role in the etiogenesis of pruritus, possibly through the release of prostaglandin D2 and increased levels of IL-31. 43 Overall, the results of this study indicate that PV basophils are constitutively activated and hypersensitive to IL-3, favoring a direct role of JAK2V617F mutation. They also lend support to the hypothesis that activated basophils contribute to pruritus in PV patients and that JAK2 inhibitors might be effective in countering this agonizing and usually treatment-insensitive symptom.…”
Section: Discussionmentioning
confidence: 55%
“…In this sense, it has recently been shown that mast cells are also involved in the malignant process of patients with myeloproliferative neoplasms and that they have an increased state of activation and release greater levels of pruritogenic factors, which might contribute to the pruritus. 27,28 In addition, there is now accumulating evidence that mast cells may play a role in atherothrombosis. 29 The observation by Pieri et al lends additional support to the notion that the JAK2 mutation promotes the activation, and not only the accumulation, of normally functional mature blood cells.…”
Section: 21mentioning
confidence: 99%
“…Intriguingly, this action in missing from epidermal keratinocytes of AD patients where TLR-2 expression is impaired [152]. Finally, it should be mentioned that in pruritic myeloproliferative disorders, mast cells release higher amount of IL-31 and other pruritogenic mediators [153].…”
Section: Inflammatory Mediators As Peripheral Itch Sensitizersmentioning
confidence: 99%